Urban and solar design potential of buildings with radial and rectangular plans (with reference to Palestine) - Al Qeek, Farid S.M. (2004)
It seems evident that the geometry of the urban form as an urban design parameter is crucial. The layout of the structure can modify the urban climate through proper design, thus improving the thermal comfort both outside and inside buildings, even reducing energy demands for heating and cooling requirements. Although solar design potentials on an architectural scale are at present well developed, the approach and the techniques applied on an urban scale are yet to be consolidated in order to promote climatic responsive urban design. This thesis is concerned with a method to evaluate solar energy in urban design. The emphasis of the thesis is to study the relationship between the urban form and solar insolation and to establish a comprehensive approach which can evaluate the urban forms, with respect to the generated shadow pattern, and can be applicable to all types of urban configurations. Among the considerations which have also been investigated, is the interrelationship between solar insolation and thermal performance of urban patterns. The thesis discusses the possible application of these forms in Palestine, in order to highlight the way that the derived results can be handled in real practice. While the analysis was mainly related to the Palestinian climate, the techniques employed may be applicable to other countries. The main structure of this thesis is arranged in two parts. The first part identifies the conceptual framework of the sustainable urban design in order to provide the reader with basic information about the subject. The principal aim of this part has been to outline the research area on which the present work was set. Secondly, parametric studies have been performed to bridge the gap in the previous studies. The parametric studies are structured into four chapters. Each study raises separate but overlapping issues and the four studies together cover the basic classified types of urban forms. The first study compares radial and rectangular forms in order to explore the solar behaviour of the radial form, as opposed to the rectangular one and to illustrate the methodology adopted in this research work to evaluate the urban forms with regard to the generated shadow patterns and thermal performance. The second study compares radial and rectangular urban canyons to clarify the influence of the self-shading effect of the radial form. The experiment evaluates the most suitable spacing between buildings to avoid overshadowing and maintain good solar accessibility. The study was also performed to determine the urban fabric that allows the achievement of high urban density under optimal solar insolation conditions. The third part contains studies related to aspects of solar insolation in bilateral types of building. The study compares different radial forms varying in the extent of their concavity to find out the one with the minimum variation of exposed areas between the two opposite facades. The final chapter of the parametric studies deals with the evaluation and analysis of the radial forms and the rectangular V-shape. This experiment aims to prove the capability of the methodology which was developed in this research, to evaluate such complex forms. Simulation studies encompass shading and thermal analyses. Based on the simulations, design recommendations were derived. The resulting framework provides a significant step forward in understanding the built environment and demonstrates the rich potential in using passive design as a means of influencing urban design. Finally, the thesis draws conclusions and identifies areas for further research into the consideration of solar energy in urban design.